Report of a Working Group on Malus/Pyrus: Fourth meeting, 7-9 March 2012, Weggis, Switzerland - Lateur, M.; Ordidge, J.; Engels, J.; Lipman, E.; Bioversity International; European Cooperative Programme for Plant Genetic Resources (2013)
The Fourth Meeting of the ECPGR Working Group (WG) on Malus/Pyrus was held 6-9 March 2012 in Weggis, Switzerland, following two ad hoc meetings on fruit synonyms and on descriptors.The ad hoc meeting on descriptors agreed draft lists of characterization and evaluation descriptors for apple and pear, including the methodology and protocols to be followed. The descriptors were then prioritized by the WG. A list of 12 validated SSR markers for apple, cherry and pear, including the methodology to apply these markers, had been previously agreed during an ECPGR ad hoc meeting. A Task Force was set up to summarize the information across Malus, Pyrus and Prunus, for publication of a manual on the ECPGR Web site. Procedures for the updating and improvement of the Malus and Pyrus Central Crop Databases (CCDBs) were agreed. The WG also discussed the perspectives of development of the CCDBs in relation to EURISCO and recommended better coordination of activities and clarification of responsibilities to ensure harmonization of data.The ad hoc meeting on synonyms obtained the following outcomes: for pear, update of the synonym list, definition and adoption of a methodology successfully implemented on 3471 accessions of the Pyrus Database; for apple, presentation of a “name-checking tool” developed alongside the Brogdale Collection Database and to be used in the development of the Malus Database. Procedures to be followed for the identification of synonyms in both the Malus and Pyrus DBs were agreed.The meeting discussed the initiative for “A European Genebank Integrated System” (AEGIS) and the establishment of the European Collection. Selection criteria were agreed: candidate accessions should originate in the holding country, and be either true to type or genetically unique. All WG members will be requested to identify within their respective collections a set of the most likely candidates. Regarding technical standards, the meeting agreed to use the final FAO Field Genebank Standards as a basis for deciding whether crop-specific standards should be developed.